Bank Risk Assessment of the Banks in Egypt - Ashraf Shehata, Guirinsky Andrey Vladimirovich, Hadir H Shubbar (International Journal of Advanced Science and Technology, 2020)
In recent years, Egypt was in a situation where the impact on the economic sector of the country is largely determined by political factors. Currently, the country’s leadership is implementing several measures aimed at stabilizing the financial sector, creating jobs, and improving the investment climate. Today, every Bank Egypt applies the risk management system based on the requirements of the Central Bank of Egypt and the recommendations of the Basel Committee. In this regard, the development and improvement of banking risk management system with the aim of eliminating them have become particularly relevant. The purpose of this article is to assess risks Bank of Egypt. Methodological basis of research is financial analysis, a comparison of coefficient method. Egypt’s banking sector has demonstrated its resilience and ability to overcome economic problems and even helped the local economy to cope with domestic and external shocks, while continuing to play its role in securing the necessary financing to support economic growth, and this is due to the effectiveness of the Central Bank in carrying out its oversight role. In addition to establishing clear rules governing the relations between banks and their clients at all stages of work, and issuing even more regulations on the hedge, what they recognized at the international level, which led to the stability of the banking sector and reduce the impact of systemic risks that can affect its integrity.